Engineering coatings : design and application - Grainger, Stan.; Blunt, Jane.; ScienceDirect eBooks (Abingdon, Cambridge : Abington Pub., 1998)
It is now 10 years since the first edition of Engineering Coatings by Stan Grainger appeared. The success of that edition, and the developments in the area since its publication make this new edition a valuable addition to the literature on the subject. This new edition describes the many methods by which surface coatings or surface modification can be carried out to delay surface degradation and prolong the useful life of engineering components. Since surface technology has advanced in many areas, new techniques such as the newer thermal spray processes and laser surfacing are now covered and the book has been expanded to include more coverage on corrosion. Major changes have also taken place in health and safety legislation, and the sections covering health and safety have been entirely revised as a result. Engineering Coatings with its breadth of coverage and sound basis in industrial practice is an invaluable guide to methods which have the potential to save money in many industries concerned with wear, corrosion, welding and thermal spraying of engineering components.
Internal combustion (piston) enginesFood; Forging; Glass; Pulp and paper; Plastics and rubber; Power generation; Steelmaking/general metal forming; Textiles; Timber; Transport; Glossary of terms used in surfacing; List of contributors; Index.
Print version record.
Elsevier
Keywords: Protective coatings; Coating processes; Coatings; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Coating processes; Coatings; Protective coatings; Electronic books